Tetrathiomolybdate alleviates bleomycin-induced pulmonary fibrosis by reducing copper concentration and suppressing EMT - Yajun Wang; Shuyang Chen; Zheng Zhou; Jinjun Jiang; Shujing Chen (European Journal of Medical Research)
Abstract Pulmonary fibrosis (PF) is a disease characterized by dysregulated extracellular matrix deposition and aberrant fibroblast activation. Emerging evidence implicates that dysregulated copper metabolism contributed to fibrotic pathogenesis, yet its role and the therapeutic potential of copper modulation remain underexplored. This study investigated the involvement of cuproptosis, a programmed cell death induced by intracellular copper overload, in PF and evaluated the therapeutic efficacy of the copper chelator tetrathiomolybdate (TTM). In a bleomycin (BLM)-induced murine PF model, intratracheal BLM administration elevated lung copper levels, upregulated oligomerized DLAT, and exacerbated fibrosis, as evidenced by collagen deposition, α-smooth muscle actin, and transforming growth factor-beta expression. TTM treatment significantly attenuated fibrotic progression, reduced oxidative stress, and suppressed Olig-DLAT accumulation. In vitro, copper ionophores induced cuproptosis in bronchial epithelial cells, characterized by reduced viability, elevated intracellular Cu⁺, and Olig-DLAT aggregation, which were reversed by TTM. Furthermore, TTM mitigated TGF-β-driven epithelial–mesenchymal transition (EMT) and fibroblast-to-myofibroblast transition (FMT), downregulating collagen-1 and restoring E-cadherin expression. These findings establish cuproptosis as a novel mechanistic contributor to PF and highlight TTM’s dual role in restoring copper homeostasis and inhibiting fibrogenic pathways, offering a promising therapeutic strategy for fibrotic lung diseases.